A Coordinated Europeanization of the Comics Industry through Distribution: The Politics of the Global Journey of Astérix and Tintin through the Strategic Distribution of their Magazines and Contents in the 1960s - Jessica Burton (On_Culture, 2019)
Researchers have usually focused on the Tintin and Astérix series’ global book diffusion through translation. However, little has been discussed about the distribution policies of the comics magazine format, a key factor in the development of European comics. This paper will consider the continentalization of western European national comics industries via the intra-EEC networking of distribution channels during the 1960s. By facilitating the exchange of comics features in the Franco-Belgian area, publishers such as Casterman, Le Lombard, and Dargaud ensured the rise of the industry and of the products they wanted to disseminate. Contemplating the motivations of publishers this article will delve deeper into the emergence of cooperative and competitive distribution channels among national publishers and between countries. Through the archives of Casterman and primary sources this article intends to contribute to a greater understanding of how the carefully planned distribution network of comics influenced the development of the European industry as a whole.